RESISTANCY TO THE LAW ENFORCEMENT OF (ASEAN) REGIONAL HUMAN RIGHTS MECHANISM, WHAT NEXT? - Dewi, Chloryne Trie Isana (Indonesian Journal of International Law, 2015)
Regional mechanism on the protection of human rights in ASEAN formally has been developed since 2007 through the adoption of the ASEAN Charter in 2007 and the establishment of the ASEAN Intergovernmental Commission on Human Rights (AICHR) in 2009. Nevertheless, efforts on the law enforcement for human rights violations committed by ASEAN citizens and/or within ASEAN territory by establishing ASEAN human rights court is hardly to achieve due to national interest of each member states. Accordingly, for the objective of achieving justice and certainty of law, cooperation among ASEAN member states should be developed through other mechanism. This article tries to identify existing situations with respect to the protection and fulfillment of human rights particularly in regards to criminal matters in the ASEAN countries. Accordingly, the article examines the responses of the Member States to the development of human rights mechanism in ASEAN. Finally, we try to propose other mechanism in regards to the protection of human rights by developing cooperation in the enforcement of international criminal law for cases related to criminal matters in particular among ASEAN countries.